Efektivitas Gaya Kepemimpinan dalam Menciptakan Lingkungan Kerja - Dawolo, Jelita; Waruwu, Meiman Hidayat; Lase, Delipiter; Eliagus Telaumbanua (Jurnal EMT KITA, 2024)
This study aims to analyze the leadership style implemented at CV Golden Mart Gunungsitoli, examine employee perceptions of this style, and identify the barriers in its application. A qualitative descriptive method was employed, involving key informants with firsthand experience regarding the company’s leadership approach. Findings indicate that leadership at CV Golden Mart tends to be centralized and control-oriented, leading to a generally negative perception among employees. Employees feel inadequately involved in decision-making processes, which negatively affects their motivation and productivity. It is recommended that company leaders adopt a more inclusive leadership approach by engaging employees in decision-making. Implementing participative leadership principles is expected to enhance employee engagement, motivation, and job satisfaction.
Keywords: Effectiveness; Leadership; Performance; Employee; Work Environment